Jet mass and substructure of inclusive jets in √s = 7TeV pp collisions with the ATLAS experiment - Anduaga, Xabier Sebastián (2012)
Recent studies have highlighted the potential of jet substructure techniques to identify the hadronic decays of boosted heavy particles. These studies all rely upon the assumption that the internal substructure of jets generated by QCD radiation is well understood. In this article, this assumption is tested on an inclusive sample of jets recorded with the ATLAS detector in 2010, which corresponds to 35 pb-1 of pp collisions delivered by the LHC at √s = 7TeV. In a subsample of events with single pp collisions, measurements corrected for detector efficiency and resolution are presented with full systematic uncertainties. Jet invariant mass, kt splitting scales and N-subjettiness variables are presented for anti-kt R = 1:0 jets and Cambridge-Aachen R = 1:2 jets. Jet invariant-mass spectra for Cambridge-Aachen R = 1:2 jets after a splitting and filtering procedure are also presented. Leading-order parton-shower Monte Carlo predictions for these variables are found to be broadly in agreement with data. The dependence of mean jet mass on additional pp interactions is also explored.